Snakehead : an Alex Rider adventure - Horowitz, Anthony, 1955- (London : walker Books Ltd, 2012)
Alex Rider crash lands off the coast of Australia where he is recruited by the Australian Secret Service to infiltrate one of the ruthless gangs operating across South East Asia, and in the midst of his dangerous mission, Alex discovers information about his parents' murder.
Booklist.
Horn Book.
School Library Journal.
5.4
5-8
Keywords: Orphans -- Juvenile fiction; Adventure and adventurers -- Fiction; Orphans -- Fiction; Spies -- Fiction; Adventure fiction; Orphans -- Fiction; Spy stories